Unveiling supply chain integration and its value in container shipping - Meersman, Hilde (2014)
Integrated supply chain management is becoming increasingly recognised as a core competitiveness for business. This is putting increased demands on freight transport services. Transport services should contribute to adding value, and the value added by transport can be significant if the operations take place in a well organised, efficient and market responsive transport system. This study aims to develop an original modelling approach for estimating supply chain value, and empirically focuses on a major world trade facilitator - container shipping. The paper presents the multivariate ordered probit/ logit models and the empirical results. Based on comprehensive literature review and conceptual theory building, a normative model for managing container shipping supply chains with the aim for better synchronisation and ultimately for value (i.e. profit for commercial setting) maximisation is proposed. A survey instrument is used to empirically verify the model with the data given by professionals from the world's top thirty container shipping lines. It is found that the level of supply chain integration is positively related to the supply chain value and profit. Overall, customer service activities are the most influential factor in affecting the supply chain value. Hence, we suggest firms to devote more resources and efforts in: 1) promoting supply chain collaboration; 2) upgrading customer service activities at strategic, tactical and operational levels. Other implications and recommendations are generated according to the empirical results.